Shedding Light on Autophagy During Human Tuberculosis. A Long Way to Go - Pellegrini, Joaquin Miguel; Tateosian, Nancy Liliana; Morelli, María Paula; García, Verónica Edith (Frontiers in Cellular and Infection Microbiology, 2022)
Immunity against Mycobacterium tuberculosis (Mtb) is highly complex, and the outcome of the infection depends on the role of several immune mediators with particular temporal dynamics on the host microenvironment. Autophagy is a central homeostatic mechanism that plays a role on immunity against intracellular pathogens, including Mtb. Enhanced autophagy in macrophages mediates elimination of intracellular Mtb through lytic and antimicrobial properties only found in autolysosomes. Additionally, it has been demonstrated that standard anti-tuberculosis chemotherapy depends on host autophagy to coordinate successful antimicrobial responses to mycobacteria. Notably, autophagy constitutes an anti-inflammatory mechanism that protects against endomembrane damage triggered by several endogenous components or infectious agents and precludes excessive inflammation. It has also been reported that autophagy can be modulated by cytokines and other immunological signals. Most of the studies on autophagy as a defense mechanism against Mycobacterium have been performed using murine models or human cell lines. However, very limited information exists about the autophagic response in cells from tuberculosis patients. Herein, we review studies that face the autophagy process in tuberculosis patients as a component of the immune response of the human host against an intracellular microorganism such as Mtb. Interestingly, these findings might contribute to recognize new targets for the development of novel therapeutic tools to combat Mtb. Actually, either as a potential successful vaccine or a complementary immunotherapy, efforts are needed to further elucidate the role of autophagy during the immune response of the human host, which will allow to achieve protective and therapeutic benefits in human tuberculosis.